Vitamin D and adrenal gland: Myth or reality? A systematic review - Al Refaie, Antonella; Baldassini, Leonardo; De Vita, Michela; Gonnelli, Stefano; Caffarelli, Carla (Frontiers in Endocrinology, 2022)
In recent years, vitamin D has become the protagonist in many studies. From cardiology to oncology the spotlight was on this vitamin. While in the past it was considered for its important role in phospho-calcium metabolism and skeletal disorders; today by studying it better, thousands of scenarios and facets have opened up on this vitamin which is actually a hormone in all respects. There are authoritative studies that demonstrate its activity in vitro and in vivo on: carcinogenesis, inflammation, autoimmunity and endocrinopathies. Its role has been studied in type 1 and type 2 diabetes mellitus, in Hashimoto or Graves’ thyroiditis and even in adrenal gland diseases. In fact, there are several studies that demonstrate the possible correlations between vitamin D and: Addison’s disease, Cushing disease, hyperaldosteronism or adrenocortical tumors. Moreover, this fascinating hormone and adrenal gland even seem to be deeply connected by common genetic pathways. This review aimed to analyze the works that have tried to study the possible influence of vitamin D on adrenal diseases. In this review we analyze the works that have tried to study the possible influence of vita-min D on adrenal disease.